Dual inhibition effect of reline deep eutectic solvent on methane hydrate nucleation and formation. (15th November 2022) - Khoo, Yau Zu; Ho, Yu-Hsuan; Chang, Kuang-Yu; Chen, Yan-Ping; Chen, Li-Jen
Graphical abstract: Highlights: DES is a new form of green solvents for flow assurance in oil and gas pipelines. Reline DES can simultaneously act as a thermodynamic and kinetic hydrate inhibitor. Inhibition effect of reline was compared to its individual components (urea and ChCl). Experimental results were correlated to Østergaard-Masoudi-Tohidi-Danesh-Todd equation. Abstract: The search for environmentally friendly hydrate inhibitors is indispensable for flow assurance to prevent hydrate formation in gas or oil pipeline. Deep eutectic solvents (DESs) are classified as a new form of green solvents due to their non-toxic and biodegradable properties. In this work, the dissociation conditions of methane hydrates influenced by reline DES, urea, and choline chloride (ChCl) were experimentally determined. Reline is derived from urea and ChCl in a 2-to-1 M ratio. The isochoric method was applied to evaluate the hydrate-liquid water–vapor-three-phase-coexisting phase boundary for ChCl (3.09 and 5.89 wt%), urea (2.58 and 5.11 wt%), and reline (5.58 and 10.43 wt%) aqueous solutions in the temperature ranging from 272.7 to 287.7 K and the pressure ranging from 2.96 to 12.78 MPa. All these three additives consistently demonstrated an inhibitory effect on methane hydrate formation. At 3.07 MPa, the dissociation temperature of methane hydrate in the presence of reline (10.43 wt%) is lower than that of the pure water system by 2.2 K. For the kinetic studies, a high-pressure micro-differential scanning calorimeter was employed for the measurement of the induction time of hydrate formation. Compared to pure water, all the studied samples demonstrated the potential to prolong the induction time of hydrate nucleation. The reline could strongly hinder the nucleation of hydrate crystals for more than 48 h. The reline DES is identified to act as both kinetic and thermodynamic inhibitors, exhibiting a dual inhibition effect on nucleation and formation of methane hydrates.